PROGRAM SAE SEBAGAI ADAPTASI KEBIJAKAN TISTAS: SMK NU TENGGARANG - BONDOWOSO (Mitra Pendidikan, 2020)
The objectives of this study were (1) to describe the implementation of the SAE program at the SMK NU Tenggarang educational institution; (2) describe the obstacles and solutions for implementing the SAE program at the SMK NU Tenggarang educational institution. This study uses a qualitative research approach, namely research that requires a deep appreciation of the interaction between concepts or in-depth analysis of the conceptual relationships that are studied empirically. In this research, data collection uses several methods such as; (a) observation, (b) documentation, and (c) in-depth interviews. The data analysis technique in this study uses three activity streams that occur simultaneously, namely; data reduction, data presentation, and drawing conclusions. The results of this study indicate that; (1) The implementation of quality free education in accordance with the expectations of the Governor of East Java's TisTas education policy can actually be carried out by every educational institution, both public and private. The key to the success of the SAE program as an adaptation of the TisTas policy at SMK NU Tenggarang is the sincere commitment to work together to build the Indonesian nation through quality free education. The spirit of mutual cooperation of all school members will reduce all forms of capitalist committees which are legacy sins of the past and cause education to be expensive for the poor, (2) the SAE program based on free education at SMK NU Tenggarang has been followed by efforts to improve the quality of education. In order to improve the quality of its education, SMK NU Tenggarang conducts several supporting activities such as; synchronizing the curriculum with DU / DI, SMK Manunggal TNI, SMK Manunggal POLRI, SMK Manunggal Desa, 1 year internship, increasing the competence of teachers and school principals, and various other quality supporters, (3) obstacles to implementing the SAE program as an adaptation of TisTas policies at SMK NU Tenggarang is more caused by external factors, in this case the carrying capacity of the people who are still shackled by local cultural wisdom.